Die deutsche Fischerei auf Köhler im Nordostatlantik 1974 - Reinsch, H.H. (1975)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010